FTA supports a better integration of bamboo into the current global climate change agenda. - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The International Network for Bamboo and Rattan publishes policy brief on the integration of Bamboo Forestry into Carbon Markets for project developers and government actors, and a Policy synthesis report on Bamboo in the Circular Economy.